Biocatalytic metal nanoparticle synthesis & investigation of catalytic properties of metal nanoparticle-enzyme hybrids - Browne, LBF (2024)
Biocatalysis and heterogeneous metal catalysis, traditionally may be thought of as very opposing fields. However recent developments in these areas have shown how combining these together can bring enhanced catalytic properties. There are now several examples of using biocatalysts and heterogeneous metal catalysts together in one-pot to provide a cascade reaction, where intermediate products do not need to be isolated and purified before the next desired step; thus, making improvements in process sustainability by cutting down the amount of waste produced. Despite homogeneous metal complexes often being found to inactivate enzymes, metals in the form of small nanoparticles (NPs) have been shown in many systems to be compatible with enzymes, therefore there is a huge area of unexplored reaction space involving both metal NPs and enzymes which may bring about very useful reaction pathways. Already demonstrated are examples where metal NPs can provide the electron source, by supply of a specific reduced “cofactor” molecule or by generating H2O2, required by the enzyme to carry out its selective transformation on an organic molecule. Combining protein structures and metals has also been carried out by either inserting artificial metal centres into proteins or by attaching metal NPs and enzymes together, often in the presence of a non-reactive support material, to make chemo-bio hybrids. To synthesise metal NPs, often very harsh conditions and/or toxic reagents are used. Therefore, alternative methods employing a bio-based material such as a plant-extract have been widely investigated, with numerous examples showing their ease-of-application. The use of a living organism (bacteria, fungi) has also been explored for the mild biosynthesis of metal NPs. Alternatively, use of an isolated enzyme has been shown to give some advantages over the plant or whole cell approach, namely due to the high uniformity of the size and shapes of the NPs which form, while still using very mild conditions for the metal reduction. Thus, in this thesis the synthesis of metal NPs by isolated enzymes is explored and the reactivity of the resulting metal NPs and enzyme hybrids is investigated. Successful well-controlled NP formation was demonstrated by supplying an enzyme (an NAD+ reductase) with its reduced cofactor, which it oxidises while reducing Au3+ salts, thereby forming Au NPs (Chapter 3). This was extended to make Au core-Pt shell NPs and the resulting metal NP-enzyme hybrids were tested for NAD+ reduction under H2, where Pt oxidises H2 and the enzyme uses those electrons generated to selectively reduce NAD+. Without the metal NP, the enzyme has no activity, and without the enzyme, Pt metal alone unselectively reduces NAD+ to a mixture of non-biologically-relevant products. Therefore, this demonstrated the synergistic behaviour of both components of the biohybrid. In a separate study (Chapter 5), another type of enzyme (a hydrogenase) was also investigated for Au NP synthesis, using H2 as the electron source, therefore providing a NP synthesis with no carbon-containing sacrificial reductant. The resulting biohybrids were then found to give increased reaction rates compared to the enzyme alone, therefore demonstrating an electron-transfer rate-enhancement effect due to contact between the enzyme and NP. This system was also investigated for synthesising a heterogeneous supported hybrid catalyst (Chapter 6) to extend the potential scope of application of these hybrids in biocatalytic processes. Another topic explored was the potential to use a significantly cheaper cofactor, riboflavin, in place of the native flavin cofactors, FMN and FAD, for applications in biocatalysis (Chapter 4). The reduction of riboflavin was tested using an efficient H2-driven process utilising the natural H2-oxidising activity of a hydrogenase enzyme and subsequently a recycling system was demonstrated for supplying reduced riboflavin to an enzyme (an ene-reductase) to allow for the chemically useful transformation of a selective alkene to alkane reduction, under mild conditions. Overall, this thesis demonstrates scope for a new class of self-assembled metal NP enzyme hybrid catalysts, whereby supplying the enzyme with its native reduced substrate (or cheaper, synthetic analogue) allowed it to control the synthesis of metal NPs. The resulting hybrid catalysts showcased advantageous catalytic properties, by combining both the enzyme and metal NP reactivities, thus offering promise for potential further catalytic applications.